The Impact of Organizational Culture on Employee Retention and Performance in the Technology Industry: A Comparative Study - Suherman, Agus; Arminarahmah, Nur; Martini, Martini (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study aims to analyze the impact of organizational culture on employee retention and performance in the technology industry, which has a high level of competition and a dynamic work environment. Using a quantitative approach, this study adopted a correlational study design and involved 300 respondents working in various technology companies in Indonesia. Data were obtained through a survey and analyzed using multiple linear regression techniques. The study results indicate that an organizational culture that supports collaboration, innovation, and personal development has a significant positive impact on employee job satisfaction and loyalty, increasing retention rates. In addition, a culture that encourages creativity and adaptation to technological changes also contributes to increased employee performance. Cultural dimensions such as managerial support and communication transparency were found to positively influence retention, while innovation and career development were shown to improve individual performance. The study also found that companies with a strong organizational culture, which emphasizes providing space for creativity and autonomous decisions, show higher retention rates, especially among young professionals. These findings underscore the importance of building and maintaining a positive organizational culture to improve employee retention and drive optimal performance in technology companies. The results of this study are expected to provide valuable insights for company leaders in designing effective organizational culture strategies to increase competitiveness in a highly competitive market.